Immigrant Women's Experiences as Mothers in the United States: A Scoping Review. Issue 1 (January 2020) - Oerther, Sarah; Lach, Helen W.; Oerther, Daniel
Abstract: Background: Immigrant mothers are raising an increasing proportion of the population of children in the United States. Purpose: The purpose of this review was to explore existing research on immigrant women's experiences of being mothers in the United States and identify key concepts, gaps in the literature, and implications for future research that builds on the strengths of immigrant women while addressing their unique challenges. Study Design and Methods: In this scoping review, Ovid MEDLINE, CINAHL, SCOPUS, Web of Science, JUSTOR, and PsycINFO databases were searched using a combination of applicable key words. Results: Twenty-two articles were selected. Few studies were identified. Analyses revealed a broad array in purpose, populations, theoretical frameworks, settings, study instruments, and practices, making comparison difficult. Although mothering is a universal experience among women who have children, little is known about the broad experiences of immigrant women from different cultures. Clinical Implications: Immigrant mothers are not a monolithic group. More research is needed to provide a deeper understanding of strengths, challenges, and solutions of various immigrant groups, which can facilitate development of nursing interventions that support immigrant women and their children in the United States, and strengthen their families. Abstract : Since 1970, the increase in U.S. births has been driven in part by immigrant mothers. While mothering is a universal experience among women who have children, little is known about the broad experiences of immigrant women from different cultures who are mothering in the United States. In this scoping review, gaps in the literature are identified and recommendations for future research are offered.